“Damaged genitals”—Cut women's perceptions of the effect of female genital cutting on sexual function. A qualitative study from Sweden - Malin Jordal; Jessica Påfs; Anna Wahlberg; R. Elise B. Johansen (Frontiers in Sociology, 2022)
Female genital cutting (FGC) is a traditional practice, commonly underpinned by cultural values regarding female sexuality, that involves the cutting of women's external genitalia, often entailing the removal of clitoral tissue and/or closing the vaginal orifice. As control of female sexual libido is a common rationale for FGC, international concern has been raised regarding its potential negative effect on female sexuality. Most studies attempting to measure the impact of FGC on women's sexual function are quantitative and employ predefined questionnaires such as the Female Sexual Function Index (FSFI). However, these have not been validated for cut women, or for all FGC-practicing countries or communities; nor do they capture cut women's perceptions and experiences of their sexuality. We propose that the subjective nature of sexuality calls for a qualitative approach in which cut women's own voices and reflections are investigated. In this paper, we seek to unravel how FGC-affected women themselves reflect upon and perceive the possible connection between FGC and their sexual function and intimate relationships. The study has a qualitative design and is based on 44 individual interviews with 25 women seeking clitoral reconstruction in Sweden. Its findings demonstrate that the women largely perceived the physical aspects of FGC, including the removal of clitoral tissue, to affect women's (including their own) sexual function negatively. They also recognized the psychological aspects of FGC as further challenging their sex lives and intimate relationships. The women desired acknowledgment of the physical consequences of FGC and of their sexual difficulties as “real” and not merely “psychological blocks”.